THE CORRELATIONS AMONG LEARNING MOTIVATION, WRITING ANXIETY AND NARRATIVE WRITING ACHIEVEMENT OF THE ELEVENTH GRADERS OF SMA ETHIKA PALEMBANG - Despita Despita; Icha Pratiwi (STKIP PGRI Lubuklinggau, 2019)
Writing English text is basic competence that students must be common to write because writing plays an important role to enable the students to describe their ideas in logical and in a communicative way. The objectives of this research were to find out whether or not there was a significant correlation between learning motivation together with writing anxiety and writing achievement. The method used was descriptive method and the design was in the form of correlational research. By using total sample, 97 students of SMA ETHIKA Palembang were chosen as the sample of this research. Two questioners and writing test were administered to collect the data. The research results show that (a) there was a positive significant correlation between learning motivation and writing achievement (r=0.845), (b) there was no significant correlation between writing anxiety and writing achievement (r=-0.053), (c) the multiple correlation analysis of all independent variables showed a positive and significant correlation (r= 0.845). Regression analysis showed that learning motivation influenced or contributed partially 84.5% to writing achievement and writing anxiety partially contributed 5,3%, the combination of learning motivation together with writing anxiety contributed 71.5% to writing achievement.